Electronic and Magnetic Properties of The Graphene/RE/Ni(111) (RE: La, Yb) Intercalation‐Like Interfaces: A DFT Analysis. Issue 6 (30th April 2022) - Guo, Qilin; Ovcharenko, Roman; Paulus, Beate; Dedkov, Yuriy; Voloshina, Elena
Abstract: The effect of the rare‐earth (RE) metals (La and Yb) intercalation on the electronic and magnetic properties of the graphene/Ni(111) interface is studied using state‐of‐the‐art density functional theory calculations. In both systems, the intercalation of RE leads to the dramatic decrease of the magnetic moments of the Ni‐interface atoms and to the negligible moments of C‐atoms in a graphene layer, compared to the parent graphene/Ni(111) system. At the same time, the significant n n ‐doping of graphene together with a band‐gap opening is observed in both cases of the RE intercalation with a position of the graphene Dirac point reaching E D − E F ≈ − 1.53 E_D-E_F≈ -1.53 eV. Also the large density of states is found in the vicinity of the Fermi level ( E F E_F ) along the M − K M-K direction for the graphene‐derived π π states which can be attributed to the joint effect of the intercalated RE and interface Ni atoms. These factors – increased density of states at E F E_F and absence of magnetism of C‐atoms in a graphene layer – indicate the possibility of the observation of the superconductive state in graphene in the considered RE‐based systems, which is important for the understanding of these and other electronics effects in the graphene‐based systems. Abstract : Intercalation of rare‐earth (RE) metals in graphene–Ni(111) leads to the restoring of the linear dispersion of the graphene π π bands and formation of the van Hove singularity in the vicinity of the Fermi level. This behavior together with the quenched magnetic moment of the underlying RE and Ni atoms could lead to the superconductivity of a graphene layer.